Do Social Dominance-Based Faultlines Help or Hurt Team Performance in Crowdsourcing Tournaments?. Issue 1 (2nd January 2022) - Cao, Fang; Wang, Weiquan; Lim, Eric; Liu, Xinmei; Tan, Chee-Wee
ABSTRACT: Firms organize tournaments on online crowdsourcing platforms to outsource complex business problems to external solvers. Participants on these platforms often self-organize into ad-hoc virtual teams to compete in such tournaments. Social dominance-based faultlines, which originate from the alignment of members based on IT-enabled social dominance attributes (e.g., rank and tier), have emerged as a novel type of faultline in crowdsourcing teams. Building on the Categorization-Elaboration Model (CEM), we investigate the contingent effects of team ability and team effort on the relationship between social dominance-based faultlines and team performance in crowdsourcing tournaments. We collected data of 265 virtual teams from Kaggle.com. We discovered that IT-enabled social dominance-based faultlines positively influence the performance of teams with low ability and high effort, whereas the effect becomes negative for teams with high ability and low effort. Our study yields theoretical implications by advancing a novel type of social dominance-based faultline and extending the CEM with two contingent factors (i.e., team effort and team ability) pertinent to team performance on crowdsourcing tournaments. We also offer practical guidelines for team formation in crowdsourcing tournaments and for the design of crowdsourcing platforms.